The effect of supportive and educational nursing care on quality of life and HE4 gene expression in patients with ovarian cancer: HE4 gene in ovarian cancer - Li, Gu; Zhang, Xiaoyu (Cellular and Molecular Biology, 2022)
Ovarian cancer is one of the most common malignancies in women and is also the fifth leading cause of cancer death in women worldwide. In recent years, the survival rate of patients with this disease has been long, and at the same time, more emphasis is on their quality of life. Therefore, the present study was conducted to investigate the effect of supportive and educational care of nurses on the life quality of patients with ovarian cancer. The expression of the HE4 gene was also evaluated as a diagnostic marker of ovarian cancer to assess the role of supportive and educational care of nurses in improving the physical health of these patients. In this study, which was a quasi-experimental study, 45 patients with ovarian cancer participated. The instrument was demographic information and quality of life questionnaires related to Beckman Institute, which were completed in two stages before and after patients’ training and support sessions. HE4 gene expression was also assessed by Real-time PCR technique. Finally, the obtained data were analyzed using SPSS software and statistical tests. Based on the results, the mean score of quality of life before the intervention was 51.73 ± 13.91, and after the intervention was 60.46 ± 13.80 (P <0.001). Also, in all four dimensions of quality of life, the mean score of individuals after the intervention increased compared to before the intervention, but this difference was recognized as significant in only two dimensions of physical and mental health (P <0.001). The results of HE4 gene expression also showed that supportive and educational care of nurses had a significant effect on the expression of this gene. Therefore, this study confirmed the positive effect of educational and supportive programs in improving the quality of life of patients with ovarian cancer. In general, the design and implementation of such programs are proposed more widely and based on patients’ educational and supportive needs.